2014
DOI: 10.1111/bcpt.12314
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes of Physicians and Pharmacists Towards International Non‐Proprietary Name Prescribing in Belgium

Abstract: International Non-proprietary Name (INN) prescribing is the use of the name of the active ingredient(s) instead of the brand name for prescribing. In Belgium, INN prescribing began in 2005 and a major policy change occurred in 2012. The aim was to explore the opinions of Dutch-speaking general practitioners (GPs) and pharmacists. An electronic questionnaire with 39 five-point Likert scale statements and one open question was administered in 2013. Multivariate analysis was performed with multiple linear regress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…However, prescribing INN drugs has certain benefits. A survey in Belgium showed that it reduced government and patient spending on pharmaceuticals and that patients even perceive INN prescribing as a way to help rationalize prescribing [ 31 ]. It also reduces the risk of confusion during dispensing [ 32 ] and facilitates communication between health professionals [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, prescribing INN drugs has certain benefits. A survey in Belgium showed that it reduced government and patient spending on pharmaceuticals and that patients even perceive INN prescribing as a way to help rationalize prescribing [ 31 ]. It also reduces the risk of confusion during dispensing [ 32 ] and facilitates communication between health professionals [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Further causes of errors included mixing up medications by the laypersons, who were sometimes disabled due to psychiatric diagnosis/senility, or the administration of two medicinal products containing the same substance which was usually due to a misunderstanding between the parents unlike in other countries where frequent switching of medicines in the pharmacy and consequent confusion of patients is associated with International Non‐proprietary Name prescription policy introduced by governments in some EU countries .…”
Section: Resultsmentioning
confidence: 99%
“…The questionnaire design was inspired elsewhere (Bearden and Mason, 1979; Dunne et al , 2014b. ; Bever et al , 2015) although new questions were introduced to accommodate for specificities of the Portuguese pharmaceutical market. Each questionnaire had three parts.…”
Section: Methodsmentioning
confidence: 99%
“…There is a growing international literature on the attitudes of physicians, pharmacists and/or patients toward generic medicines (Hassali et al , 2009; Colgan et al , 2015; Dunne and Dunne, 2015; Toverud et al , 2015; Dunne, 2016, for reviews), and also many country-specific studies: Portugal (Figueiras et al , 2008; Quintal and Mendes, 2012; Ferreira and Barbosa, 2017); Australia (Chong et al , 2011); Italy (Fabiano et al , 2012); Belgium (Bever et al , 2015); Irland (Dunne et al , 2014a, 2014b); Malasia (Chua et al , 2010); Bosnia and Herzegovina (Čatic et al , 2017); Jordan (El-Dahiyat et al , 2014); Greece (Karampli et al , 2016); Palestine (Shraim et al , 2017); India (Zaverbhai et al , 2017); Turkish (Toklu et al , 2012); Finland (Heikkilä et al , 2011); Saudi Arabia (Salhia et al , 2015); Nigeria (Auta et al , 2014; Fadare et al , 2016); Norway (Kjoenniksen et al , 2006); Japan (Kobayashi et al , 2011), France (Riner et al , 2017). The results seem to indicate that, although generic medicine use has become more widespread, many health professionals and patients hold negative perceptions of generic medicines.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation